Pemanfaatan Media Bahasa Inggris Berbasis Digital : Best Practice Di Sdn 2 Cikalang Kelas V - Nurdiani, Intan Puspita (Perspektif Ilmu Pendidikan, 2022)
Abstract: The initial condition of students at SD Negeri 2 Cikalang in implementing English learning is not optimal, mainly because learning English is not included in the local content chosen by the school so that there is no English language learning from class I. For this reason, the purpose of this article is to have English language learning with efforts to create students who are able to understand international standard languages, with the help of technology-based media so that students are expected to be able to understand more and make learning more fun. This research was carried out using the best practice method at SD Negeri 2 Cikalang, Tasikmalaya City, best practice can be defined as the most efficient and effective way to complete a task. Best Practice tells of the best experiences of creativity and innovation in overcoming the problems they face. The research technique is qualitative in which the author uses observation. The results of this study indicate that using digital-based media can improve students' vocabulary and understanding in English lessons and become an innovation in overcoming problems in English learning and inspire educators to develop more creative learning media. economical and efficient because it is a user-friendly medium. Keywords: Best Practice , English , Media , Digital , Elementary School.